A gestão democrática e os conselhos escolares na rede pública municipal de ensino de Cascavel - Pr: implantação, limites e possibilidades - Buraki, Gislaine (2017)
The assumptions of neoliberalism cooperated the structuring of State reform in 1995, making possible the reorganization of the State Administration Management under the democratic principle that is building since the promulgation of the Federal Constitution of 1988, which in Art.206, reports " The democratic management of public education in the form of the law" (BRAZIL,1998). With the law of guidelines and Bases of National Education nº 9394/1996, we find in articles 14 and 15, the regulation and organization of the insertion of the " democratic management of public education" in the form of the law, with the participation of the school and local community. In the public network of Teaching of Cascavel - PR, the discussion process about the implementation of the School Council began in 2004, however only was only effected after the approval of the Municipal Law nº 6.116, in September 12, in 2012, in municipal schools the direct and secret election for representatives of parents, teachers, servants and students for the mandate of 2013 to 2015. Based on these considerations, we intend, from documentary, bibliographical and field research, to understand and analyze the form of effectiveness and the form of effectiveness and the existing contradicictions concerning the democratic management and the School Board, as well as in which management perspective this collegiate body acts and it's interlocution with the Interative PDDE - Mechanism of the Joint Action Plan of the Ministry of Education and Culture. Field rasearch was carried out through the collections of data, using a semi- strutured questionnaire tonthe Directors (born members of the School Councils of Municipal Schools), in order to characterize the training for conselors, the possibilities and the limits in Democratic Management and Performance of the School Director. The study is based on theoretical approach that takes into account the historical context, the transformations and relations between the subjects. Throughout the research, we revealed that the emphasis on participation or the possibility of discussing some issues in order to consolidate Democratic Management. We note, therefore, that there is a lack of participation and difficulties in mobilizing the school community, since the majority of council members only obey the information and deliberations that have already been taken by the Direction or SEMED.